The Effect of the Competence of Treasury Officials and Organizational Commitment on Budget Implementation Performance (Study at Manado Regional Office XI of the State Civil Service Agency for the Period 2022–2024) - Wolontery, Dendy Aliyando; Masengi, Evi Elvira; Kantohe, Meidy (Technium Social Sciences Journal, 2025)
This study aims to analyze the effect of the competence of treasury officials (X1) and organizational commitment (X2) on Budget Implementation Performance (Y) at the Manado Regional Office XI of the State Civil Agency (BKN) during the period 2022-2024, both partially and simultaneously. This research uses a quantitative approach with data collection techniques through questionnaires to treasury officials and budget managers at Manado Regional Office XI of the State Civil Service Agency. Data analysis was conducted using descriptive statistical methods and path analysis through structural model testing (SEM-PLS). The results showed that the competence of treasury officials, which includes the Commitment Making Officer (PPK), Pay Order Signing Officer (PPSPM), and Treasurer, has a positive and significant influence on Budget Implementation Performance at Manado Regional Office XI of the State Civil Service Agency. These competencies include technical skills, regulatory knowledge, and mastery of financial information systems such as Financial Application System at the Agency Level (SAKTI) and State Treasury and Budget System (SPAN), which crucially contribute to state financial management. In addition, the level of organizational commitment is also proven to have a moderate positive influence on Budget Implementation Performance. This commitment encourages employees to put in voluntary and loyal efforts in achieving organizational goals, which overall improves work unit performance in efficiency, effectiveness and compliance with budget regulations. Simultaneously, the competence of treasury officials and organizational commitment provide a strong prediction of the Budget Implementation Performance of the Manado Regional Office XI of the State Civil Service Agency. However, Budget Implementation Performance is also influenced by external factors not examined in this study, showing the complexity in the context of public budget management.